Design and Development of a Tractor Operated Garlic Harvester - Krishna, Khambe Vishal; De, Dipankar; Sahoo, P. K. (Journal of Agricultural Engineering, 2014)
India although being the second largest producer of garlic, the crop productivity is low as compared to the world average. Low level of mechanization is a major factor of low productivity in India. Harvesting is one of the important operations in garlic cultivation. In India, it is performed manually which is time consuming and labour unavailability during peak harvesting seasons makes the task more difficult. A 4-row tractor operated garlic harvester was designed and developed for mechanical harvesting of garlic. Digging unit of the harvester consisted of a V-shape blade having width, length and thickness of 600 mm, 300 mm, and 10 mm, respectively. Soil separator unit was of 1000 mm long, 650 mm wide, with10 mm diameter rods spaced at 50 mm. Mean harvesting percentage of 96.12, plant damage of 5.94%, soil separation index of 0.26, power requirement of 4.54 kW and field capacity of 0.24 ha.h-1 with field efficiency of 68.7% were recorded for the harvester under field condition.